Cost- and energy-efficient manufacture of gears by laser beam melting. (May 2018) - Kamps, Tobias; Lutter-Guenther, Max; Seidel, Christian; Gutowski, Timothy; Reinhart, Gunther
Abstract: The decision for choosing a manufacturing technology for a specific product is primarily based on cost in industrial practise. Current government regulations together with international projects like the Convention on Climate Change introduce further factors targeting a sustainably choice of manufacturing sequences. A typical measure is total energy embedded in a product based on the employed manufacturing route. Hence, industrial decision makers may have to assess both a cost- and energy-efficient production sequence. This results in the main challenge of an early estimation of manufacturing costs and energy consumption for choosing the most suitable production scenario. This is a crucial point to an industrial implementation of additive manufacturing (AM) and specifically for expensive and energy-intensive technologies for industrial metal processing like laser beam melting (LBM). This includes a consideration of both the entire process sequence embedded in a suitable production scenario and potential for product redesign derived from the use of LBM. This paper suggests two integrated models for cost and life cycle assessment in a cradle-to-gate framework focussing an industrial process sequence. Gear wheel manufacturing in a low volume or high variant production scale is chosen as a production scenario. Three industrial process sequences for gear production based on machining, hobbing, and LBM are investigated. Special focus is set to the impact of lightweight design on energy- and cost-efficiency of the manufacturing sequence. The key factors influencing cost- and energy-intensity are identified recommending a production scenario that is worthwhile for LBM for the small scale production of gears. It is concluded that both cost- and energy-efficiency have to be assessed with different process alternatives in order to identify a worthwhile scenario for LBM based on cost and life cycle assessment models. Lightweight design is identified as the most significant factor for reducing costs and energy-consumption that suggests employing lightweight design for cost- and energy-efficiency. The intended audience of this contribution are scientists, industrial applicants of LBM and conventional gear manufacturers.